Exploring and overcoming obstacles to academic-industry knowledge diffusion: a framework - Ho, Yew Joe; Nurhamiza Mumin @ Osman (RMP Publications, 2019)
This paper explores the plausible challenges of knowledge diffusion, particularly the transmission of novel academic findings to their ultimate utilization or adoption in the industry. The paper focuses on the more restrained but not less important issues that impede such development and proposes that solution to the lack of reliability in measuring knowledge diffusion hinges on methodological improvement; the disinclination of human factor in technology acceptance could be understood and potentially rectified with the Technology Acceptance Model (TAM) instrument; and the hindrance of less-accessible medium for knowledge diffusion could be resolved with a more simplified medium, specifically the Online-Video-Platform (OVP) journal.